Nurturing Trust Through Faith-Based Service: Implementation of Islamic Service Strategies and Customer Interest - Nurul Huda; Angrum Pratiwi; Iqbanul Hakim (Asian Journal of Law and Islamic Finance, 2025)
This study examines the implementation of Islamic service strategies at BPRS Bhakti Sumekar Pratama Ra'as Branch and their impact on customer interest in Barokah savings products. Using a qualitative approach with data collected through interviews, observation, and document analysis, the research identified four key service dimensions: responsiveness, reliability, assurance, and empathy. The findings reveal that these dimensions, when infused with Islamic principles such as ihsan, amanah, sidq, and maslahah, create a distinctive service experience that resonates with customers' religious values while addressing practical financial needs. Supporting factors include community receptiveness to Islamic banking concepts, product accessibility features, and cultural alignment of service approaches. Conversely, inhibiting factors comprise limited public understanding of Islamic banking principles, geographical constraints affecting service reach, and competition from conventional banking institutions. The study contributes theoretical insights into the practical application of Islamic service principles in rural banking contexts while providing actionable implications for Islamic banking practitioners seeking to enhance service quality and customer relationships.